Voicing their choices: Advance care planning with adolescents and young adults with cancer and other serious conditions. Issue 4 (August 2022) - Wiener, Lori; Bedoya, Sima; Battles, Haven; Sender, Leonard; Zabokrtsky, Keri; Donovan, Kristine A.; Thompson, Lora M. A.; Lubrano di Ciccone, Barbara B.; Babilonia, Margarita Bobonis; Fasciano, Karen; Malinowski, Paige; Lyon, Maureen; et al.
Abstract: Objectives: To determine whether engaging in advance care planning (ACP) using a formal tool, Voicing My CHOiCES (VMC), would alleviate adolescent and young adults (AYAs) anxiety surrounding ACP and increase social support and communication about end-of-life care preferences with family members and health care providers (HCPs). Methods: A total of 149 AYAs aged 18–39 years receiving cancer-directed therapy or treatment for another chronic medical illness were enrolled at seven US sites. Baseline data included prior ACP communication with family members and HCPs and measures of generalized anxiety, ACP anxiety, and social support. Participants critically reviewed each page of VMC and then completed three pages of the document. ACP anxiety was measured again immediately after the completion of VMC pages. One month later, participants repeated anxiety and social support measures and were asked if they shared what they had completed in VMC with a family member or HCP. Results: At baseline, 50.3% of participants reported that they previously had a conversation about EoL preferences with a family member; 19.5% with an HCP. One month later, 65.1% had subsequently shared what they wrote in VMC with a family member; 8.9% shared with an HCP. Most (88.6%) reported they would not have had this conversation if not participating in the study. No significant changes occurred in social support. There was an immediate drop in anxiety about EoL planning after reviewing VMC which persisted at 1 month. Generalized anxiety was also significantly lower 1 month after reviewing VMC. Significance of results: Having a document specifically created for AYAs to guide ACP planning can decrease anxiety and increase communication with family members but not necessarily with HCPs. Future research should examine ways ACP can be introduced more consistently to this young population to allow their preferences for care to be heard, respected, and honored, particularly by their healthcare providers.